Comparative evaluation of the effectiveness of nsaids in treatment of patients with back pain depending on the bone mineral density - Orlik, Tatyana; Povorozniuk, Vladyslav; Kreslov, Yevgen (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To compare the effectiveness of using of nonsteroidal anti-inflammatory drugs (NSAIDs) for reducing the severity of back pain in older patients depending on the bone mineral density (BMD). Methods: The study involved 45 postmenopausal female patients aged 46–75 years divided into groups: I (main) — with osteopenia / osteoporosis, II (comparison) — with normal BMD. The presence and intensity of pain were evaluated by means of 4-component visual analogous scale (VAS) and McGill questionnaire. BMD was measured by dual energy X-ray absorptiometry. Comparative assessment between the groups was carried out using the criterion of efficiency. Influence of therapy on treatment outcome was evaluated in terms of the size of the effect (effect size, ES). Results: After 14 days of treatment patients in both groups showed decreasing in the severity of back pain. Against the background of complex treatment with using of celecoxib in women in group I reliable dynamics determined according to all indeces of McGill questionnaire and VAS, in patients of group II revealed no reliable changes in the indices of descriptors and grades. Severity of pain at the time of the survey decresed in the I group on 54.7 %, in the II — on 61.5 %. According to calculation of criteria on efficiency reduction in the severity of pain in patients in group I marked on the index ranks which reliably more decreased in the group of women who took celecoxib compared to the group of diklofenac. Patients of group II according to VAS reliably higher criteria of effectiveness using celecoxib compared with diclofenac were determined. Conclusion: In treatment of patients with back pain and reduced BMD celecoxib with its efficacy prevails a little bit over diclofenac but the drug of choice for patients in this category can be any NSAID. In patients with normal BMD celecoxib proved more effective compared to diclofenac. To choose an anesthetic drug for the treatment of this group it is necessary depending on clinical situation and expected effect.